The relationship between acute stress and neurophysiological and behavioral measures of food-related inhibitory control: An event-related potential (ERP) study. (1st March 2022) - Allen, Whitney D.; Rodeback, Rebekah E.; Carbine, Kaylie A.; Hedges-Muncy, Ariana M.; LeCheminant, James D.; Steffen, Patrick R.; Larson, Michael J.
Abstract: Stress influences many health-related behaviors including diet and nutrition intake, often resulting in increased calorie intake, fewer healthy eating behaviors, and poorer nutrition. Food intake is modulated by inhibitory control and has important implications for our physical, mental, and emotional health. Yet, little is known about the relationship between stress and food-related inhibitory control. We tested the influence of a short-term experimental stressor on behavioral and event-related potential (ERP; N2 and P3 components) measures of food-related inhibitory control. Ninety-seven healthy participants were randomly assigned to complete the Trier Social Stress Test (TSST) (n = 48, 27 females [52.9%]) or a neutral control condition (n = 49, 35 females [70%]) immediately followed by food-specific go/no-go and neutral go/no-go tasks while electroencephalogram (EEG) data were recorded. Stress levels were successfully manipulated, with heightened self-report and physiological measures (heart rate and systolic blood pressure) of the stress response in individuals who completed the TSST compared to control. As expected, the high calorie food-specific go/no-go task elicited larger N2 amplitude than the neutral task. N2 component amplitude was also significantly larger following the TSST relative to the control task. There were no significant between-group or task differences for P3 amplitude or behavioral measures. Findings suggest heightened N2 amplitude following psychological stress that is not specific to food or inhibition processes and may reflect heightened arousal following stress. Future research in individuals with overweight/obesity or experiencing chronic stress will further clarify the role of stress in food-related inhibitory control. Highlights: Participants were randomly assigned to Trier Social Stress Test or neutral condition. Heart rate and blood pressure showed clear stress-condition differences. Food-specific event-related potential (ERP) measures were larger for the TSST group than the neutral group. Stress was associated with larger overall N2 ERP, but this was not specific to food. Behavioral performance did not differ between stress and control groups.